The Terminology of Thuma’ninah in the Qur’an: Al Qurtubi’s Interpretation and Mental Health Relevance - Nur ‘Alim Muhammad Kautsar; Jihan Kharisma Hidayatulloh; Ainur Rhain (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rising cases of stress, anxiety, and mental health disorders highlight the growing need for inner tranquillity. The Qur’an introduces the concept of al-thuma’ninah, yet its meanings across different verses have not been comprehensively examined through the lens of classical exegesis. Previous studies largely focus on semantic or contemporary approaches, leaving a gap in understanding how classical scholars conceptualised thuma’ninah. This study addresses this gap by analysing the meaning of al-thuma’ninah according to al-Qurtubi’s Tafsir al-Jami‘ li Ahkam al-Qur’an, using qualitative library research and thematic analysis of Qur’anic verses derived from the root ط-م-أ-ن. The research aims to identify the categories of thuma’ninah and explore their relevance to mental health. The findings show that al-thuma’ninah is a multidimensional concept encompassing epistemological reassurance, psychospiritual calm, steadfast faith under pressure, social stability, and illusory worldly tranquillity. These results affirm its relevance as a spiritual foundation for modern mental well-being.